2015
DOI: 10.1007/s13224-014-0665-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Hysterectomies: Our 10 Years Experience in a Single Laparoscopic Center

Abstract: Study Objective To evaluate the association between outcomes of laparoscopic hysterectomy with respect to clinical factors, intraoperative variants, and post-operative complications. Design The study conducted was retrospective (Canadian Task Force Classification II-1). Setting The set used in this study was a gynecological laparoscopic centre. Patients The present study included 858 women who underwent laparoscopic hysterectomies with or without bilateral/unilateral salpingo-oophorectomy, from December 2004 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…8 This was much higher compared to the study by Bettaiah et al where it was 0.9%. 9 A complication rate of 4.5% was reported by O'Hanlan et al 10 Hoffman et al, had a major complication rate of 5.6%, while Heinberg et al, had a major complication rate of 14.4%, and Chapron reported complications in 10%. [11][12][13] Urological complication in the present study was 1 (0.84%) case of bladder injury.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…8 This was much higher compared to the study by Bettaiah et al where it was 0.9%. 9 A complication rate of 4.5% was reported by O'Hanlan et al 10 Hoffman et al, had a major complication rate of 5.6%, while Heinberg et al, had a major complication rate of 14.4%, and Chapron reported complications in 10%. [11][12][13] Urological complication in the present study was 1 (0.84%) case of bladder injury.…”
Section: Discussionmentioning
confidence: 93%
“…Conversion rate reported by Bettaiah R et al was 0.93% and Vaisbuch E et al was 1.8%. 9,26 Conversion rate of 10.9% was reported by Sinha R et al where conversion was required for intractable hemorrhage, bladder injury and inability to reach all pedicles. 27 There is similarity between this study and the present study regarding the reasons for conversion.…”
Section: Discussionmentioning
confidence: 96%
“…8 Ramesh et al reported fibroid (54.4%) to be the most common cause of hysterectomy. 9 The concomitant surgical procedures that were done with this LAVHs didn't prolong the operative time except in cases of vaginal repair. The same was noticed by other surgeon.…”
Section: Discussionmentioning
confidence: 93%
“…According to recent publications the overall complication rate of all hysterectomy methods is about 1-4.5% depending on the source [ 6 9 ]. In one of the recent studies intraoperative complications in the abdominal group occurred in 7.4% of cases, followed by vaginal (3.9%) and laparoscopic (3.7%) groups [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the recent studies intraoperative complications in the abdominal group occurred in 7.4% of cases, followed by vaginal (3.9%) and laparoscopic (3.7%) groups [ 8 ]. Other studies presented the hysterectomy conversion rate as 0.93% and the complication rate as 0.9% (mostly total laparoscopic hysterectomies) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%